Women writers and the English nation in the 1790s: Romantic belongings - Keane, Angela (Cambridge University, 2013)
Angela Keane addresses the work of five women writers of the 1790s and its problematic relationship with the canon of Romantic literature. Refining arguments that women's writing has been overlooked, Keane examines the more complex underpinnings and exclusionary effects of the English national literary tradition. The book explores the negotiations of literate, middle-class women such as Hannah More, Mary Wollstonecraft, Charlotte Smith, Helen Maria Williams and Ann Radcliffe with emergent ideas of national literary representation. As women were cast into the feminine, maternal role in Romantic national discourse, women like these who defined themselves in other terms found themselves exiled - sometimes literally - from the nation.